Stroke and Ischemic Heart Disease among LGBT Sexual and Gender Minorities in Japan - Katagiri, Aomi; Tokuda, Yasuharu; Taniguchi, Kiyosu; Shibuya, Kenji; Tabuchi, Takahiro (Journal of Public Health Sciences, 2024)
Leading causes of death in Japan include stroke and ischemic heart disease (IHD). It has been unclear regarding risk for these diseases among sexual and gender minorities (SGMs) in Japan. Using cross-sectional data from JACSIS (Japan COVID-19 and Society Internet Survey) 2022, participants were categorized in cisgender/heterosexual, lesbian, gay, bisexual and transgender based on sex at birth, gender identity and sexual orientation. Outcome was measured by past history of stroke or IHD. Multivariable logistic regression was constructed adjusting for risk factors. 24,298 participants were eligible for analysis. Overweight/obesity was prevalent among gay and bisexual participants, while lesbians and transgenders were implausible compared to cisgender/heterosexuals. After adjusting for potential covariates, all SGM groups experienced increased prevalence of stroke (transgender odds ratio [OR], 2.97; 95% CI, 1.74-5.06, gay OR, 2.69; 95%CI, 2.00-3.64, lesbian OR, 2.44; 95%CI, 1.0-3.40, bisexual OR, 1.86; 95% CI, 1.01-3.40) and IHD (transgender OR, 2.92; 95%CI, 1.75-4.86, gay OR, 2.18; 95%CI, 1.64-2.91, lesbian OR, 1.96; 95%CI, 1.32-2.93, bisexual OR, 1.23; 95% CI, 0.65-2.31) compared to cisgender/heterosexuals. SGMs in Japan have different prevalence of cardiovascular risk factors compared to Western countries. SGMs face higher prevalence of stroke or IHD, and transgenders were most vulnerable. There is much need in support for the health of SGMs in Japan.